Is intravesical instillation of hyaluronic acid and chondroitin sulfate useful in preventing recurrent bacterial cystitis? A multicenter case control analysis - Giorgio Gugliotta; Gloria Calagna; Giorgio Adile; Salvatore Polito; Salvatore Saitta; Patrizia Speciale; Stefano Palomba; Antonino Perino; Roberta Granese; Biagio Adile (Elsevier, 2015)
Objective: Urinary tract infections (UTIs) are common in the female population and, over a lifetime, about half of women have at least one episode of UTI requiring antibiotic therapy. The aim of the current study was to compare two different strategies for preventing recurrent bacterial cystitis: intravesical instillation of hyaluronic acid (HA) plus chondroitin sulfate (CS), and antibiotic prophylaxis with sulfamethoxazole plus trimethoprim. Materials and methods: This was a retrospective review of two different cohorts of women affected by recurrent bacterial cystitis. Cases (experimental group) were women who received intravesical instillations of a sterile solution of high concentration of HA + CS in 50 mL water with calcium chloride every week during the 1st month and then once monthly for 4 months. The control group included women who received traditional therapy for recurrent cystitis based on daily antibiotic prophylaxis using sulfamethoxazole 200 mg plus trimethoprim 40 mg for 6 weeks. Results: Ninety-eight and 76 patients were treated with experimental and control treatments, respectively. At 12 months after treatment, 69 and 109 UTIs were detected in the experimental and control groups, respectively. The proportion of patients free from UTIs was significantly higher in the experimental than in the control group (36.7% vs. 21.0%; p = 0.03). Experimental treatment was well tolerated and none of the patients stopped it. Conclusion: The intravesical instillation of HA + CS is more effective than long-term antibiotic prophylaxis for preventing recurrent bacterial cystitis.